Fostering quranic literacy and promoting reading habits: the role of quranic reading house in pasi village, Berampu District, Dairi Regency - Sihombing, yuan alfinsyah (Talenta Publisher Universitas Sumatera Utara, 2025)
Pasi Village, located in Berampu District, Dairi Regency, North Sumatra Province, covers an area of 12.50 km², accounting for approximately 30.60% of the total regency area. Although the majority of its population is Muslim, both the proficiency in reading the Qur’an and the general reading culture among the community remain relatively low. The only reading facility available, the Arke Menjaha Reading House—established by the local mosque congregation—faces limited resources and low community engagement. This community service initiative aims to foster reading interest, particularly among children, and to improve the ability to read the Qur’an accurately. To achieve these objectives, a Participatory Action Research (PAR) approach was implemented through three stages: problem identification via collaborative discussions, program implementation involving literacy development and Qur’anic reading training, and impact evaluation. Interventions included expanding the book collection, providing illustrated reading materials, and applying the talaqqi tahsinul Qur’an method. The results indicated a 70% increase in reading house visitors (ages 6–15), and participant attendance in the Qur’anic reading sessions reached 75–100% across 6 of the 8 planned meetings. This initiative is expected to support the sustainability of learning and encourage the spread of Qur’anic reading skills among village children.